Analisis Profesionalisme News Anchor Najwa Shihab dalam Menarik Minat Menonton - Delta Septiasmara; Aliasan Aliasan; Lena Marianti (Social Science and Contemporary Issues Journal, 2023)
And methods a news anchor uses to present information that the audience likes. The title of this study is Analysis Of The Professionalism Of News Anchor Najwa Shihab To Attract Viewing Interest. This study discusses the news anchor Najwa Shihab who is also the host of the Mata Najwa program, which has existed since 2008 until now which is also aired on Najwa Shihab's YouTube and media company Narasi TV. This study aims to analyze the professionalism of news anchor Najwa Shihab in attracting viewing interest. The research used in this study begins with data collection, observation, recording interpretations, and application of the properties and objects under study, which are included in a descriptive quantitative approach that uses the semiotic theory of Roland Barthes. The subject of this study was a video show of the Mata Najwa program hosted by Najwa Shihab, aired on 'Najwa Shihab's YouTube channel. This method forms data from the behavior that has been observed according to the aspect of professionalism. After analyzing, it is known the professionalism of news anchor Najwa Shihab in attracting interest in watching someone and how he packages a program like Mata Najwa that persists with achievements and a trusted image for the community.